The Endocannabinoid System across Postnatal Development in Transmembrane Domain Neuregulin 1 Mutant Mice - Chesworth, Rose; Long, Leonora E.; Weickert, Cynthia Shannon; Karl, Tim (Frontiers in Psychiatry, 2018)
Cannabis use is a well-established component risk factor for schizophrenia, particularly in adolescent individuals with genetic predisposition for the disorder. Alterations to the endocannabinoid system have been found in the prefrontal cortex of patients with schizophrenia. Thus, we assessed whether molecular alterations exist in the endocannabinoid signalling pathway during brain development in a mouse model for the schizophrenia risk gene neuregulin 1 (Nrg1). We analysed transcripts encoding key molecules of the endocannabinoid system in heterozygous transmembrane domain Nrg1 mutant mice (Nrg1 TM HET), which is known to have increased sensitivity to cannabis exposure. Tissue from the prelimbic cortex and hippocampus of male and female Nrg1 TM HET mice and wild type-like (WT) littermates was collected at postnatal days (PND) 7, 10, 14, 21, 28, 35, 49 and 161. Quantitative polymerase chain reaction was conducted to assess mRNA levels of cannabinoid receptor 1 (CB1R), and enzymes for the synthesis and break down of the endocannabinoid 2-arachidonoylglycerol [i.e. diacylglycerol lipase alpha (DAGLα), monoglyceride lipase (MGLL) and α/β-hydrolase domain-containing 6 (ABHD6)]. No sex differences were found for any transcripts in either brain region; thus, male and female data were pooled. Hippocampal and cortical mRNA expression of DAGLα, MGLL, and ABHD6 increased until PND 21-35, and then decreased and stabilised for the rest of postnatal development. Hippocampal CB1R mRNA expression increased until PND 21, and decreased after this age. Expression levels of these endocannabinoid markers did not differ in Nrg1 TM HET compared to control mice at any time point. Here, we demonstrate dynamic changes in the developmental trajectory of several key endocannabinoid system transcripts in the mouse brain, which may correspond with periods of endocannabinoid system maturation. Nrg1 TM HET mutation did not alter the developmental trajectory of the endocannabinoid markers assessed, suggesting other mechanisms may be responsible for the exaggerated cannabinoid susceptibility in these mice.